2013
DOI: 10.1186/1471-2393-13-65
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention of gestational diabetes for women who are overweight and obese: a randomised controlled trial

Abstract: BackgroundGestational Diabetes Mellitus (GDM) has well recognised adverse health implications for the mother and her newborn that are both short and long term. Obesity is a significant risk factor for developing GDM and the prevalence of obesity is increasing globally. It is a matter of public health importance that clinicians have evidence based strategies to inform practice and currently there is insufficient evidence regarding the impact of dietary and lifestyle interventions on improving maternal and newbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
2
0
2
Order By: Relevance
“…While many studies have reported distinct effects of type 2 diabetes on the auditory system, none have investigated the effects of gestational diabetes on the auditory system. Recognised maternal complications of gestational diabetes include an increased risk of developing type 2 diabetes, metabolic syndrome and cardiovascular diseases 16 , 17 . Altered glucose metabolism in pregnancy may influence inner-ear physiology to resemble that seen in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have reported distinct effects of type 2 diabetes on the auditory system, none have investigated the effects of gestational diabetes on the auditory system. Recognised maternal complications of gestational diabetes include an increased risk of developing type 2 diabetes, metabolic syndrome and cardiovascular diseases 16 , 17 . Altered glucose metabolism in pregnancy may influence inner-ear physiology to resemble that seen in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Obez gebeler ise; düşük yapma, ölü doğum, preeklampsi, sezeryanla doğum, hipertansiyon, enfeksiyon ve tromboembolik hastalık gibi birçok gebeliğe bağlı durumlarla karşı karşıya kalabilmektedir. 37 Bebeğin gelişim sürecinde gebede birçok hormon düzeyinde değişiklik oluşmaktadır. Özellikle östrojen, kortizol, progesteron, prolaktin gibi hormonların serumdaki artışı insülin düzeyine olan ihtiyacı arttırmaktadır.…”
Section: Gestasyonel Diabetes Mellitusunclassified
“…Bir milyon sekiz yüz seksen dört gebe üzerinde yapılan bir kohort çalışmada (Tablo 4); normal ağırlığa sahip olan gebelerde GDM gelişim riski %4 iken, obez olan gebelerde bu risk %19 olarak belirtilmiştir. [37][38][39]…”
Section: Gestasyonel Diabetes Mellitusunclassified
“…Peer support has shown to be successful for both patients with diabetes and patients with complex pregnancies. Programs include a variety of strategies such as group classes, phone calls, and text/e-mail check-in systems [9,17]. Multiple studies for non-pregnant adults with diabetes include peer coach interventions in which a patient with well-controlled disease is given extra training to reach out to patients in their communities [4,18,20].…”
Section: Introductionmentioning
confidence: 99%